Proceedings of the 7th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2019
DOI: 10.7712/120119.7211.20160
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Shear and Moment Demands in Reinforced Concrete Wall Buildings

Abstract: This research aims to obtain envelopes of the moment and shear demands in reinforced concrete (RC) wall buildings subjected to ground motions. These envelopes are intended to be used for designing RC buildings. Three research buildings with non-rectangular walls designed according to Eurocode 8 are considered. The seismic performance of the buildings is evaluated from nonlinear response history analysis (NRHA) with increasing levels of ground motion intensity. The RC walls are simulated with a model with distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Story masses showed in Table 1 were adjusted to obtain first-mode elastic periods representative of real wall structures. This consideration is not trivial since, as shown by Morales (2017) and Morales et al (2019), previous studies with similar modelling approaches have resulted in building models with first-mode elastic periods larger than what is expected from real structures. The periods of the buildings from this study are compared against the expressions proposed in ASCE 7-10 (2010) and in Massone et al (2012), the latter based on the values measured by Wood et al (1987).…”
Section: Description Of the Analytical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Story masses showed in Table 1 were adjusted to obtain first-mode elastic periods representative of real wall structures. This consideration is not trivial since, as shown by Morales (2017) and Morales et al (2019), previous studies with similar modelling approaches have resulted in building models with first-mode elastic periods larger than what is expected from real structures. The periods of the buildings from this study are compared against the expressions proposed in ASCE 7-10 (2010) and in Massone et al (2012), the latter based on the values measured by Wood et al (1987).…”
Section: Description Of the Analytical Modelmentioning
confidence: 99%
“…An exception is presented by Quintana (2018), who proposes a relationship between the elastic displacement and a dynamic amplification factor, that is used in the capacity design for shear of cantilever walls (Paulay and Priestley, 1992), and that is a function only of the number of stories in the building. However, more recent studies have demonstrated that the dynamic amplification factor depends on the ductility demand too (Priestley et al, 2007;Morales, 2017;Jiménez et al, 2019;Morales et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Para garantizar el mecanismo deseado en los muros es fundamental usar envolventes de diseño para momentos y corte, de esta manera se evita la incursión no-lineal fuera de la base de los muros y fallas frágiles; se recomienda diseño al corte por capacidad en muros. Envolventes de diseño, que incluyen la influencia de los modos superiores de vibrar, pueden hallarse en diversos códigos de diseño (Eurocode 8, 2004;NZS 3101, 2006) y en la literatura técnica (Paulay y Priestley, 1992;Priestley et al, 2007;Morales et al, 2019).…”
Section: Diseño De Elementos De Hormigón Armadounclassified